Educomunicação: novo paradigma de educação na sociedade em rede e a constituição - Andrade, Camila Santos (2007)
This present study tackles the importance of social intervention in the educational process: the Educommunication in the Society. The subject is developed through the use of descriptive and explanatory bibliographic research with a brief analysis of the History of Education. Following this, the educational crisis and Jacques Delors four educational bases are discussed. It is then analyzed the fundamental right to education, subjective pubic right, in the Constitution as a programmatic rule that has immediate applicability in order to consolidate the Democratic Rule of Law. Through this, particularities of such Society and the tendency of the globalized world are verified. It is then discussed the relevance of mitigating the apprentice s errors, value the multiplicity of individual talents, which is the educational purpose across lifetime. The last chapter discusses about the importance of adopting the Educommunication, the intermediary agent which unifies education, communication and technology in the educational process, whose media related instrumental leads to the use of educommunicative practices, organized by the communicative ecosystem in the Society. At last, this study aims to point the Educommunication s purposes through the use of multidisciplines and with the educommunicator s help in order to fully develop the individual granting him citizenship